An Analysis of Students' Mathematical Problem-Solving Ability at Class VII Social Arithmetic Materials Based on Learning Styles - Joko Soebagyo; Istikharoh Istikharoh; Huri Suhendri; Khoerul Umam (Lembaga Penelitian dan Pengabdian Masyarakat Universitas Indraprasta PGRI, 2022)
Learning style is an activity of thinking, processing, and understanding something that is preferred and has the characteristics of each person. Problem-solving ability is a skill that needs to be possessed in the process of solving mathematical problems. This study aims to describe students' problem-solving abilities on social arithmetic material in terms of learning styles. The research was conducted through a descriptive qualitative research design. The population is all seventh-grade students of MTs Al-Khairiyah, South Jakarta. Sampling using a total sampling technique. Then three students were selected, namely students who scored the highest visual, auditory and kinesthetic learning styles. The instrument uses a learning style questionnaire and a test of problem-solving skills and semi-structured interviews—data analysis techniques with data reduction, exposure, and concluding to explain mathematical problem-solving abilities. The findings of this study are students with the highest scores of visual, auditory, and kinesthetic learning styles can solve social arithmetic problems based on Polya's steps without any significant differences, only from different styles when solving problems